Effect of Moringa oleifera leaf on the efficiency to increase protein supply to ruminants (Bangladesh Journal of Animal Science, 2015)
Moringa oleifera leaf was investigated for nutritional quality, presence of tannins and its activity using polyethyelene glycol (PEG) and in vitro study of protein degradation in the rumen. The antibiotic growth promoter (AGP), Monensin was used as an external control to compare with the degradation of Moringa leaves. The different forms of tannin content in Moringa leaves were very negligible. Total phenol, total tannin, condensed tannin and hydrolysable tannin contents of Moringa leaves were 3.92±0.42, 1.19±0.14, 0.57±0.06 and 0.07±0.02 mg/g, respectively. The in vitro gas production, organic matter digestibility (OMD%) and metabolizable energy (ME) content of Moringa leaves were 54.39 ml, 77.44% and 11.14 MJ/kgDM, respectively. There were no significant differences in gas production, in vitro OMD% and ME content in the presence of tannin binding agent PEG. These results indicated that the different forms of tannin present in Moringa leaves are not active tannins, therefore, feeding Moringa leaves are safe for the ruminant animals. The kinetic study of in vitro gas production with Moringa leaves and Monensin showed almost similar results and there was no significant difference among them but higher values were found in the control indicated that Moringa leaves have the ability to inhibit the breakdown of protein in the rumen as of Monensin. On the contrary, soluble protein concentration was increased 182% with the addition of Moringa leaves compared to control and the values were almost close (213%) with Monensin during the 12h incubation period. The pellet protein concentration was also increased (119%) with Moringa leaves and Monensin (115%) compared to control although there was no significant difference between them. Therefore, it can be concluded from the present findings that feeding Moringa leaves appeared to be an alternative source of protein and are safe for ruminant animals. Moringa leaves have been shown to alter favorably ruminal protein fermentation characteristics thus spare protein by a decreased breakdown/deamination of protein/amino acids that functions as of Monensin.DOI: http://dx.doi.org/10.3329/bjas.v44i1.23142              Bang. J. Anim. Sci. 2014. 44 (1): 46-51